Impact of Different Types of Cancer on Health-Related Quality of Life - Raed Abdullah Alharbi, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: Cancer is known as a condition that some cells in the body can uncontrollably proliferate and spread to other body's parts. Although various studies have shown a link between cancer and patient quality of life, this cross-sectional study has investigated the impact of different types of cancer along with treatment status on HRQoL including physical and mental health, in adult cancer patients. Methods: The impact of cancer on HRQoL in adult patients in this cross-sectional study used data provided from Behavioral Risk Factor Surveillance System, 2020 in the United States. BRFSS is a health, behaviors, and social life questionnaires of people in the United States provided by Centers for Disease Control and Prevention (CDC). There were 401,958 participants in this questionnaire. To achieve the study's purpose, the Statistical Analysis System (version 9.4) was used to conduct several statistical approaches, including descriptive, inferential, and predictive methods. Results: Of the 401,958 participants in the BRFSS 2020, 22,551 were adult patients with cancer with different status of treatment. This study showed that cancer with different treatment status has a statistically significant impact on HRQoL in adult patients. Conclusion: Cancer has a significant impact on physical and mental health in adult patients. Different status of treatment can increase the impact on physical health problems to be increased by 70.08% and mental health problems to be increased by 74.02%.